The Potential of Digital Ethnography for Sensitive Topics and Hidden Population - Delli Paoli, Angela (Italian Sociological Review, 2022)
In this paper we investigate the potential of digital research when the digital is both the topic and the instrument of research. The digital is an interesting topic of social research when technology intersect society, that is in those fields where technology give new rise to some social issues directly impacting mainstream social problems (such as identity and sexuality). In the case of sexuality, for example, the digital offers discursive spaces to legitimate sexual minorities identities, especially when their sexual models do not conform to social norms. For these topics digital ethnography may be a distinctive method to study social change deriving from the digital. It seems to be particularly appropriate to study phenomena born digital and to investigate generative and productive (and not just reflective) digital identities and cultures avoiding the contrived situation of an interviewer asking people direct questions and allowing to document the performative use of language. In other words, it gives access to sensitive topics and hidden population which would otherwise be less visible. [...]